The Influence of Customer Relationship Management and Social Media on Customer Loyalty in E-Commerce with Brand Image as a Moderator - Muhammad Junaid Kamaruddin (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
This study was conducted to test the effect of customer relationship management and social media on customer loyalty with brand image as a moderator. This study shows that customer loyalty has a strong relationship with customer relationship management, social media, and brand image. This study describes how relationships with customers can be managed well so that customer loyalty is achieved. The sample that has been tested is 155 people who have shopped in e-commerce. This research was carried out by utilizing the structural equation modeling analysis method on Smart PLS (Partial Least Square) software. The results presented that Customer Relationship Management has a positive and significant effect on Customer Loyalty, Socia Media has a positive and significant effect on Customer Loyalty, Brand Image has a positive and significant effect on Customer Loyalty, Brand Image Moderation strengthens the positive and significant effect of Customer Relationship Management on Customer Loyalty, Brand Image Moderation weakens the positive and significant effect of SocialMedia on Customer Loyalty. It is hoped that further research can add new variables to make it better.